Personal individuality in the modern world: a loss of identity (Actual Problems of Mind, 2017)
The paper analyses modern manifestations of a personal individuality. The authors conclude that drive to a disgraceful behavior and eccentricity conceals a crisis of individuality and exhibits a global anthropological crisis.
Keywords: Personal identity; identity; deindividualization; social alienation; anthropological crisis